ANALISIS KEBUTUHAN TITIK LAMPU UNTUK PENERANGAN OPTIMAL DI DAERAH WISATA DESA LES - Putri Siswanto, Fagita; Putra Winaya, Ida Bagus; Resa Guna Winangun, Nyoman Gede; Gunantara, Nyoman; Sukerayasa, I Wayan; Arsa Suyadnya, I Made; Mataram, I Made; Dharma, Agus; Dyana Arjana, I Gede (Jurnal SPEKTRUM; Vol 11 No 4 (2024): Jurnal SPEKTRUM, 2024)
Optimal lighting in tourist areas is a crucial factor in enhancing visitor comfort and safety, especially during the night. This study aims to calculate the required number of light points in Les Village, a developing tourist area, to achieve optimal lighting. Based on the calculations, 54 light points are needed to illuminate the area. Each light point uses a 5-watt LED lamp, selected for its energy efficiency and ability to provide adequate illumination. The placement of the light points was determined by considering the even distribution of light, reducing dark areas, and supporting the aesthetics of the surrounding environment. This study is expected to serve as a reference for planning lighting systems in other tourist areas with similar characteristics.